Emergence hour-by-hour of r-process features in the kilonova AT2017gfo - Sneppen, Albert; Watson, Darach; Damgaard, Rasmus; Heintz, Kasper E.; Vieira, Nicholas; Väisänen, Petri; Mahoro, Antoine (EDP Sciences, 2025)
The spectral features in the optical/near-infrared counterparts of neutron star mergers (kilonovae, KNe) evolve dramatically on hourly timescales. To examine the spectral evolution, we compiled a temporal series that was complete at all observed epochs from 0.5 to 9.4 days of the best optical/near-infrared (NIR) spectra of the gravitational-wave detected kilonova AT2017gfo. Using our analysis of this spectral series, we show that the emergence times of spectral features place strong constraints on line identifications and ejecta properties, while their subsequent evolution probes the structure of the ejecta. We find that the most prominent spectral feature, the 1 μm P Cygni line, appears suddenly, with the earliest detection at 1.17 days. We find evidence in this earliest feature for the fastest yet discovered kilonova ejecta component at 0.40-0.45c. Across the observed epochs and wavelengths, the velocities of the line-forming regions span nearly an order of magnitude, down to as low as 0.04-0.07c. The time of emergence closely follows the predictions for Sr II because Sr III combines rapidly under local thermal equilibrium (LTE) conditions. The transition time between the doubly and singly ionised states provides the first direct measurement of the ionisation temperature. This temperature is highly consistent with the temperature of the emitted blackbody radiation field at a level of a few percent. Furthermore, we find the KN to be isotropic in temperature, that is, the polar and equatorial ejecta differ by less than a few hundred Kelvin or ≲5%, in the first few days post-merger based on measurements of the reverberation time-delay effect. This suggests that a model with very simple assumptions, with single-temperature LTE conditions, reproduces the early kilonova properties surprisingly well.